If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 9 = -2 Reorder the terms: 9 + Y = -2 Solving 9 + Y = -2 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + Y = -2 + -9 Combine like terms: 9 + -9 = 0 0 + Y = -2 + -9 Y = -2 + -9 Combine like terms: -2 + -9 = -11 Y = -11 Simplifying Y = -11
| 8(6x-1)=6x+1 | | -(6y+1)-(5y-8)=1 | | -79-10x=7*23 | | u-3u=10+8 | | y=-11+6x | | 8+5m-1=9m+11-3 | | 8v=-7 | | 3(x+2)+2(3x+2)=28 | | 2(4-2x+x^2)-x(x+2)= | | 33x-10-17x=4(4x-3)+2 | | 1+3n-5n=12 | | 6r-4r=16 | | 8x+14x=132 | | 16x^2+38x-5=0 | | (3x+5)-(-7x+8)= | | 2y-3x=0 | | 5(3+6x)-5=70 | | -7g=49 | | 4(4x+2)=20-2(x-3) | | x^4-81-x^3+9=0 | | -7(3-x+3)=-18 | | 58q-2.8-5.2q=-0.4-2.2 | | 2x^2-24x+81=0 | | 14x^2+40x-6=0 | | x-7.6=-6.5 | | 12=-24y | | 4x+40=13x-68 | | r+33=14 | | -2t^2-6t+5=0 | | 5y-2+y+48=5y+50-1y | | 5x=165 | | 6x+34=14x+30 |